Fatty acid metabolism complements glycolysis in th selective regulatory t cell expansion during tumor growth - Pacella, I.; Procaccini, C.; Focaccetti, C.; Miacci, S.; Timperi, E.; Faicchia, D.; Severa, M.; Rizzo, F.; Coccia, E.; Bonacina, F.; Mitro, N.; Norata, Giuseppe; et al. (National Academy of Sciences, 2018)
The tumor microenvironment restrains conventional T cell (Tconv) activation while facilitating the expansion of Tregs. Here we showed that Tregs’ advantage in the tumor milieu relies on supplemental energetic routes involving lipid metabolism. In murine models, tumor-infiltrating Tregs displayed intracellular lipid accumulation, which was attributable to an increased rate of fatty acid (FA) synthesis. Since the relative advantage in glucose uptake may fuel FA synthesis in intratumoral Tregs, we demonstrated that both glycolytic and oxidative metabolism contribute to Tregs’ expansion. We corroborated our data in human tumors showing that Tregs displayed a gene signature oriented toward glycolysis and lipid synthesis. Our data support a model in which signals from the tumor microenvironment induce a circuitry of glycolysis, FA synthesis, and oxidation that confers a preferential proliferative advantage to Tregs, whose targeting might represent a strategy for cancer treatment.